Note of interview between Mr J.M. Batista i Roca and Mr H.V. Tewson - Batista i Roca, Josep Maria, 1896-1978; Tewson, Vincent
017a-0031-001 CONFIDENTIAL Sept 1938 Note of Interview between Mr. J.M. Batista i Roca and Mr. H.V. Tewson. Mr. Batista i Roca stated that in Spain they had succeeded in forming the representative parties of the Left into a Left Republican Union. Included in this party was the Federal Party, Republican Union Basque Nationalist Party Catalan Left Republican Party Democratic Union (Catholic but anti-Fascist) Roca said that the Socialists did not link up, but that Praeto [ Prieto ] was very sympathetic There are quarrels between Negrin and the Socialists on account of his taking many actions without consultation. The recent changes of the Spanish Government were to get rid of representatives of the new Movement referred to above, and it has resulted that for the first time since 1931 the Catalan Left Republican Party has been left out of the Government Cabinet. Other members who have resigned from the Government are the Governor of the Bank of Spain, the Under-Secretary for Foreign Affairs, and the President of the Council of State. The members of the Catalan Left Republican Party has been replaced by a Catalan Communist, and it is interesting to note that out of a Parliament of 80, 61 belong to the Catalan Left and there are only 5 Communists. Roca asks - why then a Communist in the Cabinet? The Basque Representative who has resigned was the only Catholic. The main purpose of Roca's visit was to ascertain whether Sir Walter could secure any support from the U.G.T. for the new Movement. I told Roca he would appreciate that we did not desire to interfere too much in the internal affairs of Spain. Contact was difficult, and all I could promise would be that I would mention to Sir Walter the points that he had raised. HVT/CB. 292/946/17a/31